HLA ligandome analysis of primary chronic lymphocytic leukemia (CLL) cells under lenalidomide treatment confirms the suitability of lenalidomide for combination with T-cell-based immunotherapy. (3rd April 2018) - Nelde, Annika; Kowalewski, Daniel J.; Backert, Linus; Schuster, Heiko; Werner, Jan-Ole; Klein, Reinhild; Kohlbacher, Oliver; Kanz, Lothar; Salih, Helmut R.; Rammensee, Hans-Georg; Stevanović, Stefan; Walz, Juliane S.
ABSTRACT: Recent studies suggest that CLL is an immunogenic disease, which might be effectively targeted by antigen-specific T-cell-based immunotherapy. However, CLL is associated with a profound immune defect, which might represent a critical limitation for mounting clinically effective antitumor immune responses. As several studies have demonstrated that lenalidomide can reinforce effector T-cell responses in CLL, the combination of T-cell-based immunotherapy with the immunomodulatory drug lenalidomide represents a promising approach to overcome the immunosuppressive state in CLL. Antigen-specific immunotherapy also requires the robust presentation of tumor-associated HLA-presented antigens on target cells. We thus performed a longitudinal study of the effect of lenalidomide on the HLA ligandome of primary CLL cells in vitro . We showed that lenalidomide exposure does not affect absolute HLA class I and II surface expression levels on primary CLL cells. Importantly, semi-quantitative mass spectrometric analyses of the HLA peptidome of three CLL patient samples found only minor qualitative and quantitative effects of lenalidomide on HLA class I- and II-restricted peptide presentation. Furthermore, we confirmed stable presentation of previously described CLL-associated antigens under lenalidomide treatment. Strikingly, among the few HLA ligands showing significant modulation under lenalidomide treatment, we identified upregulated IKZF-derived peptides, which may represent a direct reflection of the cereblon-mediated effect of lenalidomide on CLL cells. Since we could not observe any relevant influence of lenalidomide on the established CLL-associated antigen targets of anticancer T-cell responses, this study validates the suitability of lenalidomide for the combination with antigen-specific T-cell-based immunotherapies.